THE BEARING CAPACITY OF PEAT SOIL WITH BAMBOO REINFORCEMENT - Waruwu, Aazokhi; Widjajakusuma, Jack; Denzel, Brian; Calvin, Fransiscus (GEOMATE Journal, 2024)
Peat soil is a type of soil that has low bearing capacity and high settlement, which has an unfavorable effect on construction. Peat soils require a reinforcement system of micropile-reinforced slabs. One alternative material that can be used as a micropile is bamboo. This study aims to determine the impact of bamboo micropiles on increasing bearing capacity, modulus of subgrade reaction, and reducing settlement. This research was conducted by testing a physical model on peat soil reinforced with bamboo micropiles and concrete micropiles as a comparison. The lengths of the piles used were 10 cm, 20 cm, 30 cm, and 40 cm, respectively, which were installed on a 30 cm x 30 cm slab. The plate load test is conducted on the slab to obtain the bearing capacity. The results showed that micropiles could increase bearing capacity and reduce settlement. The bearing capacity of slabs with bamboo micropiles was close to that of concrete micropiles, or about 0.92 times the bearing capacity of concrete micropiles. The primary difference between the two materials was the rougher surface of the concrete micropile, which provided higher shaft friction than the bamboo micropile. The subgrade reaction's initial and secant moduli were 170 and 50 times the bearing capacity, respectively. Settlement reduction due to pile installation was relatively high at the initial loading and constant at higher loads.